Coastal zone as a space of foreign arrival tourism in 2000-2017 - Krzysztof Parzych (Nicolaus Copernicus University in Toruń, 2019)
This study addresses the development of foreign incoming tourism in the coastal tourist zone of the Baltic coast. Quantitative and spatial analysis of foreign incoming tourism in coastal communes of the Baltic coast in the period 2005-2017 was carried out. The GUS Local Data Bank data on the number of foreign tourists using the accommodation base of the number of overnight stays for foreign tourists in all 38 coastal communes in the Baltic Sea Coast were used as source material for the implementation of the research problem. The material was analyzed statistically and cartographically in the form of cartograms. The analysis of the spatial distribution of foreign tourists and overnight stays in individual coastal municipalities indicates their strong concentration in the spa communes (Kołobrzeg, Świnoujście, Międzyzdroje, Sopot), in Gdańsk and in communes with well-developed accommodation infrastructure and accompanying services (Rewal, Darłowo, Dziwnów). The least visited are rural communes, located on the outskirts of the region, with poorly developed tourist infrastructure, with a dominant function of socio-economic development, different from the tourist one.